Erythrocyte SOD1 activity, but not SOD1 polymorphisms, is associated with ICU mortality in patients with septic shock - Costa, Nara Aline [UNESP]; Cunha, Natália Baraldi [UNESP]; Gut, Ana Lucia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP]; Reis, Bruna Zavarize; Fernandes, Ana Angelica Henrique [UNESP]; Rogero, Marcelo Macedo; Norde, Marina Maintinguer; Minicucci, Marcos Ferreira [UNESP] (Elsevier, 2018)
The objective of our study was to evaluate the influence of the superoxide dismutase 1 (SOD1) polymorphisms on erythrocyte SOD1 activity and the mortality of patients with septic shock. We prospectively evaluated 175 patients aged over 18 years with septic shock upon ICU admission. However, 38 patients were excluded. Thus, 137 patients were enrolled in the study. Blood samples were taken within the first 24 h of the patient's admission to determine erythrocyte SOD1 activity and nine SOD1 gene polymorphisms. The mean patient age was 63 ± 16 years, 58% were men, and ICU mortality rate was 66%. The patients who died were older and more severely ill, with higher Acute Physiology and Chronic Health Evaluation (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores, as well as higher lactate, urea, and protein carbonyl levels. In the logistic regression model, erythrocyte SOD1 activity was associated with ICU mortality. This relationship was also maintained in the highest tertile of SOD1 activity (odds ratio [OR]: 0.02; 95% confidence interval [CI]: 0.00–0.78; p = 0.037). Only SNP rs2070424 of the SOD1 gene influenced erythrocyte SOD1 activity. For patients with the AA allele, the activity of SOD1 was lower in relation to G-carriers (A/G+G/G genotype) (p = 0.019). None of the nine SOD1 SNPs were associated with ICU mortality. In conclusion, the SNP rs2070424 of the SOD1 gene interferes with erythrocyte SOD1 activity, and higher activity of SOD1 was associated with decreased mortality in patients with septic shock.
Keywords: Oxidative stress; Septic shock; SOD1 activity; SOD1 polymorphisms